Effects of Land Uses on Soil Quality Indicators: The Case of Geshy Subcatchment, Gojeb River Catchment, Ethiopia - Melku Dagnachew; Awdenegest Moges; Asfaw Kebede Kassa (Applied and Environmental Soil Science)
Land degradation caused by improper land use management is a critical worldwide problem that has revived the issue of resources sustainability. Soil degradation, which involves physical, chemical, and biological degradation, is the key component of land degradation. Assessment of soil quality (SQ) indicators that distinguish soil degradation in different land use (LU) types is enviable to achieve sustainable land management strategies. The objective of this study was to assess the effects of land uses on soil quality indicators in the Geshy subcatchment of the Gojeb River Catchment, Omo-Gibe Basin, Ethiopia. The LU types identified for evaluation included natural forest, cultivation, and grazing lands. Accordingly, a total of 54 soil samples (three LU types × three slope classes (blocks) × three replications × two soil depths) were collected with an “X” plot design for data analysis. Statistical differences in SQ indicators were analyzed among LU types, slope classes, and soil depths and tested using univariate analysis of variance and Pearson’s correlation coefficient, following the general linear model. The results showed that a number of SQ indicators were significantly influenced by LU changes and soil depths. The sand, dry soil bulk density ρb, volumetric soil water contents (VSWC), total porosity, water infiltration rates, cumulative infiltration, and total nitrogen showed significant variations between the natural forest and the other LU types and soil depths (p<0.05). However, silt, clay, soil pH, SOC contents, carbon-to-nitrogen ratio, and available phosphorus did not show significant variations between LU types and soil depths (p>0.05). The overall qualities of the soils under the cultivation land were inferior in VSWC, TP, water infiltration rates, SOC contents, and TN soil attributes of the adjacent natural forest and grazing lands. The studied soils were found to be dominantly of clays with slightly acidic and low SOC contents and slow in their infiltration rate. Thus, integrated and sustainable land management, aimed at enhancing proper LU systems, is crucial for the sustainable ecosystem functioning and is the most effective way in reversing of soil quality deterioration.